Enemy of all mankind : a true story of piracy, power, and history's first global manhunt - Johnson, Steven, 1968- (Riverhead Books, 2020)
"How did a single manhunt spark the modern era of multinational capitalism? Henry Avery was the seventeenth century's most notorious pirate. The press published wildly popular--and wildly inaccurate--reports of his nefarious adventures. The British government offered enormous bounties for his capture, alive or (preferably) dead. But Steven Johnson argues that Avery's most lasting legacy was his inadvertent triggering of a new model for the global economy. Enemy of All Mankind focuses on one key event--the attack of an Indian treasure ship by Avery and his crew--and its surprising repercussions across time and space. Johnson uses the extraordinary story of Henry Avery and his crimes to explore the emergence of the modern global marketplace: a densely interconnected planet ruled by nations and corporations. Like the bestselling How We Got To Now and The Ghost Map, Enemy of All Mankind crosses disciplinary boundaries to recount its history: the chemistry behind the invention of gunpowder; the innovations in navigation that enabled the age of exploration; the cultural history of pirates; the biographical history of Avery and his crew; the rise of the Moghul dynasty; and the commercial ambition of the East India Company. In this compelling work of history and ideas, Johnson deftly traces the path from a single struck match to a global conflagration"--